A study of role of B scan ultrasound in posterior segment pathology of eye - Agrawal, Rekha; Ahirwal, Sushma (International Journal of Medical Research and Review, 2015)
Introduction: Ophthalmic ultrasonography has become the most important accurate diagnostic imaging modality for directly evaluating lesions of posterior segment having opaque ocular media. Study was conducted to assess the role of B scan ultrasound in posterior segment pathology of eye. Material and Method: This prospective study was conducted in Department of Radiodiagnosis, NSCB Medical College and Hospital, Jabalpur from October 2013 to October 2014.The study included patients referred for high resolution ultrasonography from Department of Ophthalmology. 50 patients were subjected to clinical Ophthalmological examination and B scan USG evaluation. Results: The cases were divided according to age ranging from 0-80 years. Maximum no. of patients studied was in 5th decade (22%). Male predominance was seen with sex ratio 3.1:1 (M:F). Loss of vision and redness of eye were the leading symptoms. Maximum no. of ocular abnormalities studied were of Vitreous (40.2%) followed by Retina (25.77%). Also Among vitreous abnormalities, Vitreous hemorrhage was the most common accounting for 56.41% cases followed by vitreous detachment (33.33%), vitreous band was found in 10.25% cases. Retinal detachment was the common retinal abnormality detected (41.5%), while retinoblastoma was seen in 5.66 % cases. Cataract is the most commonly encountered lens abnormality. 81.81% eyes had cataract among total lens abnormalities followed by dislocation of lens (18.18% among lens abnormalities). Choroidal abnormalities include maximum cases of choroidal detachment (80%), while choroidal hemorrhage was seen in 20%. Conclusion - From, the present study it was noted that B-scan is very efficient tool in diagnosing various ocular abnormalities. B-scan can categorize the lesions in the posterior chamber well, depending on the echotexture and anatomy. Even the exact location of the lesion can be well made out.